Integrasi Sistem Manajemen ISO 9001, ISO 22000, dan HAS 23000 dan Penerapannya di Industri Pengolahan Susu - Putra Aviva Ivada; Joko Hermanianto; Feri Kusnandar (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
The fragmented management system of quality (ISO 9001), food safety (ISO 22000), and halal assurance (HAS 23000) requires a lot of allocated resources in a food company. This study aimed to develop an Integrated Management System (IMS) that ful ll the three management systems. For a case study, the implementation of IMS model and its effectiveness was evaluated in PT IPS. The IMS model consists of 16 main clauses and 24 sub-clauses. Quantitative data showed that PT IPS met 56% of IMS sub-clauses. In order to fully implement the IMS model, PT IPS needed to set up a strategy to assign priority scale for each criteria. Socialization to personells is important to improve their understanding and awareness as well to improve involvement of various authorities to determine risk assessments, especially on the change control processes that impacted on the decreasing bureaucracy obstacles. Furthermore, PT IPS also needed to improve planning, employee’ empowerment, establish rules and procedures and apply hierarchical structure of the organization. In the scale of importance, emphasizing on the advantages of IMS implementation to top and middle managements is important to increase the motivation of employees. The IMS model successfully eliminates working time, reduced operating cost and minimized third-party audit findings.